The Influence of Safety Knowledge, Safety Climate, Safety Motivation on Safety Performance - Wijaya, Nurhayat Rokhmat; Brahmasari, Ida Aju; Ardiana, I Dewa Ketut Raka (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
The ILO estimates that around 2.3 million people die every year due to work accidents or illnesses. In Indonesia, claims for Work Accident Insurance and Death Benefit increased from 2019 to November 2023, especially in the construction services industry. During the Lombok Power Plant FTP 2 construction project throughout 2023, has occurred near misses, property damage, first aid and fire were found. Safety performance is a general method for determining the effectiveness and adequacy of work management safety systems. This research aims to analyze the relationship between safety performance and several variables that have been studied previously, including safety knowledge, safety climate, safety motivation in the Lombok Steam Power Plant FTP 2 construction workers. This research uses a quantitative research approach which emphasizes data in the form of numbers and processing it using the Structural Equation Modeling (SEM) method. The population in this study was 278 Lombok Power Plant FTP 2 Construction workers for the March 2024 period with a sample of 165 workers. The research results show that (1) safety knowledge has a significant effect on safety performance, (2) safety climate has an insignificant effect on safety performance, (3) safety motivation has a significant effect on safety performance